2009
DOI: 10.1053/j.ajkd.2009.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Soluble ST2 Protein in Idiopathic Nephrotic Syndrome Recurrence Following Kidney Transplantation

Abstract: France.DS and JD contributed equally to this work. No differences were detected in these sera before transplantation. Moreover, recurrent patients displayed the same sST2 isoform as the two control groups. In vitro, a mouse podocyte cell line was profoundly altered by incubation with sera of recurrent patients. However, purified sST2 from these patients was not able to reproduce these damages. In addition, induction of high sST2 levels in rats did not trigger proteinuria. Collectively, these data suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Nevertheless, unequivocal identification of a single factor as the decisive permeability-inducing and disease-causing factor in the FSPF has not yet been established. Therefore, it seems reasonable to assume that several factors interact or act in sequence to induce FSGS, some of which may even act indirectly to induce posttransplantation recurrence without directly influencing permeability, such as sST2 (53). In addition to the fact that the FSPF(s) are still elusive, the mechanisms of their accumulation in the circulation are so far unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, unequivocal identification of a single factor as the decisive permeability-inducing and disease-causing factor in the FSPF has not yet been established. Therefore, it seems reasonable to assume that several factors interact or act in sequence to induce FSGS, some of which may even act indirectly to induce posttransplantation recurrence without directly influencing permeability, such as sST2 (53). In addition to the fact that the FSPF(s) are still elusive, the mechanisms of their accumulation in the circulation are so far unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ST2 is found to be selectively expressed on a subset of Th2 cells but not Th1 cells and mediates Th2 functions [2]. A recent study has indicated that elevated sST2 seems to be a consequence of renal pathologies not involved in the pathogenesis of idiopathic nephrotic syndrome [26]. Although patients with recurrence expressed a normal sST2 isoform, elevated serum sST2 suppresses IL-6, IL-12, and TNF-α production via inhibition of NF-kB activation and mitogen-activated protein kinase pathways to result in the development of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity for elevated sST2 in CKD is consistent with the relative predominance of the immune inflammatory response. Also, a recent study suggests that sST2 protein is a marker of idiopathic nephrotic syndrome recurrence [26].…”
Section: Discussionmentioning
confidence: 99%
“…This spliced isoform is produced by antigen presenting cells such as monocytes and macrophages and acts as decoy receptor and thus antagonizes the effects of IL-33 [119,120]. In fact, patients suffering chronic inflammatory diseases have high levels of soluble ST2 [121,122].…”
mentioning
confidence: 99%